Pidana Perampasan Kemerdekaan Mandiri sebagai Jenis Pidana Alternatif untuk Mengurangi Kelebihan Populasi (Overpolulation) Narapidana di Lembaga Pemasyarakatan dan Beban Pemerintah - Angkasa (Perspektif Hukum, 2020)
The population in Indonesia’s correctional institution presents an alarming situation, because as of August 25, 2020, with a capacity to hold 133,169 prisoners, however, the total population stands at 232.585 prisoners. It is showing that the national prison population increased dramatically with an occupancy rate of 75 %. Not only is this causing a negative impact that can lead to prisonization that are counterproductive to the purpose of the imprisonment, but violating human rights. Many of the regulations contained in the criminal law such as restorative justice in the juvenile justice system or restorative justice formulated on Indonesian National Chief Police Regulation Number 6 of 2019 concerning criminal investigation are actually can be used to reduce the entry of the prisoner to the correctional institution but has not yet been done significantly. There are also many regulations to reduce the prison population such remission, leave before released or conditional release, but the methods do not appear to be able to significantly reducing population in the correctional institution and this condition leads to the violations of the human rights of prisoners and it is contradicting to the purposes of the imprisonment. Theoretical study using the library research method based on secondary data is conducted and concluded that a new form of criminal sentence can be suggested which has not been regulated yet in the country’s existing criminal law or formulated in Indonesia draft’s criminal code. A new form of criminal sentence is self-funded deprivation of liberty, which means taking someone’s freedom away based on a court judgment decided that someone is deprived of their liberty if they are legally proven guilty to have committed a crime. The enforcement of the self-funded deprivation of the liberty carried out by keeping the offender to stay in their house or in other designated places. The costs borne entirely by the crime offender and their families and the offender is also not permitted to leave home, and that the supervision from the correctional centers (BAPAS) and community may also be instituted.